The Effect of Medialization Procedures on Laryngopharyngeal Reflux in Patients With Glottic Insufficiency: A Preliminary Study - Gaddam, Sriprachodaya; DeSilva, Trevor; Funk, Zachary; Gardi, Adam; Mullen, Katherine; Chi, Hye Rhee; Hawkshaw, Mary J; Ramadan, Omar; Sataloff, Robert T (Journal of voice, 2025)
SummaryObjectiveTo evaluate whether medialization procedures performed for management of glottic insufficiency also reduce patients’ concurrent laryngopharyngeal reflux (LPR) signs. Study DesignRetrospective chart review. MethodsA retrospective chart review was conducted of patients who visited the office of the senior author, received a diagnosis of glottic insufficiency and LPR, and were offered medialization procedures. Patients were categorized into two groups: those who received medialization surgery ( n = 39) and those who did not ( n = 40). Reflux finding scores (RFS) collected pretreatment and post treatment were compared between groups. 24-hour pH-impedance results also were evaluated pretreatment and post treatment when available. ResultsNo significant changes were found in RFS between preintervention and postintervention within either the medialization group or the non-medialization group. Between-group comparisons showed no significant differences in RFS pre-and postintervention for each of the subcategories. Patients in the medialization group showed improvement in 24-hour pH-impedance testing with decreased total reflux events (mean reflux events pre = 59; mean reflux events post = 39) as well as total upright reflux events (mean reflux events pre = 47; mean reflux events post = 16) at the proximal sensor. However, these improvements were not statistically significant ( P = 0.12, P = 0.17, respectively). ConclusionMedialization procedures in patients with glottic insufficiency may not improve the laryngeal effects of LPR. Further research with more subjects is encouraged to determine whether treating glottic insufficiency may also improve LPR symptoms.